INVITRO ANTI-OXIDANT ACTIVITY OF HORDEUM VULGARE LEAF - SOWJANYA KATTUPALLI (International Journal of Phytomedicine, 2019)
Objective: Objective of the present study was to carry out in-vitro anti-oxidant activity of Hordeum vulgare belonging to family Poaceae Methods: The shade dried stem part of H. vulgare (1 kg) was powdered and extracted with chloroform, petroleum ether, ethanol and aqueous using soxhletion. The extract were concentrated using rotary evaporator under reduced pressure at 40 °C, till free from the solvents and thereby providing crude extracts which was subsequently employed for further studies. the antioxidant activity of Hordeum vulgare leaf using DPPH* radical scavenging model and to assess the antioxidant activity of Hordeum vulgare leaf and stem using Nitric oxide free radical (NO*) scavenging model and to assess the antioxidant activity of Hordeum vulgare leaf using superoxide free radical (SO*) scavenging model and to assess the antioxidant activity of Hordeum vulgare leaf using hydroxide free radical (OH*) scavenging model. Results: The graph was extrapolated between concentrations of the plant extracts and % of inhibition to find out the 50% inhibition concentration. The extracts were exhibited dose dependent neutralization of DPPH*, NO*, SO* and OH* free radicals and activity was compared with standard curcumin. The IC 50 of 310 µg, 620 µg, greater than 640 µg/ml ethanolic extract of Hordeum vulgare stem against of DPPH*, NO*, SO* and OH* free radicals, respectively. This indicates the ethanolic extract Hordeum vulgare leaf exhibited antioxidant activity. Conclusion: The antioxidant activity was exhibited due to presence of flavonoids and tannins, phenolic compounds which was present methanolic extract of Hordeum vulgare